PENGARUH MODEL NHT BERBANTU MEDIA ULAR TANGGA TERHADAP HASIL BELAJAR SISWA KELAS IV DI SD N 02 UJUNG PANDAN JEPARA - Firda Zulfana, Purwadi, dan Mudzanatun (Universitas PGRI Yogyakarta, 2020)
AbstractThis study aims to determine the effect of snake-media media-assisted NHT (Number Head Together) model on the learning outcomes of Grade IV students in theme 6 sub-theme 1 in SD Negeri 02 Ujung Pandan Jepara Year 2018/2019. This type of research is quantitative research in the form of a Pre-Experiment Design with the design of the Pretest-Posttest One Group. The population in this study were all fourth grade students of SD Negeri 02 Ujung Pandan Jepara. The sample taken was 22 fourth grade students with Probability Sampling technique in the form of saturated sampling. The data in this study were obtained through tests, documentation, and questionnaires. The results showed that the percentage of posttest classical learning completeness (91%) was more than the percentage of classical learning completeness pretest (32%) and based on the results of one-party t test it was known that tcount was more than t table (9.413> 1.721). From these results it can be concluded that H0 is rejected. In other words there is a positive influence on snake-media media-assisted NHT (Number Head Together) learning model on the learning outcomes of class IV theme 6 sub-theme 1 in SD Negeri 02 Ujung PandanKeyword: NHT Model, Snake Media Ladder, Learning Outcomes.